FORTIFIKASI TEPUNG TULANG IKAN BANDENG (Chanos chanos) DALAM PEMBUATAN KUE KERING - Darmawangsyah Darmawangsyah; Jamaluddin P Jamaluddin P; Kadirman Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2016)
The purpose of this study was to determine the chemical and hedonic quality pastries that have been fortified with fish bone meal. This study uses a Completely Randomized Design (CRD), which consists of four treatment concentration, ie, without the addition of fish bone meal (control), the addition of fish bone powder 8%, 10% and 12%. The parameters observed in this study is the moisture content, ash content, calcium content, and hedonic value pastries. Data were analyzed by analysis of variance and if significantly different DMRT followed by a further test. The results of this study showed that the greater the concentration of fish bone meal will increase the value of ash and calcium levels pastries. However, all treatments had higher levels of water that meets quality standards. The test results showed the treatment hedonic increasing concentration of fish bone meal effect on the texture, aroma, and taste pastries produced. The best treatment is the pastry with the addition of 10% fish bone meal with calcium level of 1.21%